Metabolic hormonal alterations in functional hypothalamic amenorrhea and anovulation associated with Polycystic ovary syndrome - Jamwal, Shalini; Soni, Abhishek (Journal of Applied Pharmaceutical Research, 2024)
Background: Polycystic ovary syndrome (PCOS) is a multifaceted endocrine disorder affecting many women during their reproductive years. It is characterized by oligo/amenorrhea, anovulatory cycles, polycystic ovaries, and insulin resistance. This review explores the hormonal and metabolic alterations associated with PCOS, comparing them to functional hypothalamic amenorrhea (FHA). Key aspects include the abnormally high LH pulse frequency in PCOS, indicating hyperactive gonadotropin-releasing hormone (GnRH), and the role of hyperandrogenemia in exacerbating the condition by increasing LH pulse secretion from the pituitary gland. Additionally, the review examines the neuroendocrine basis for PCOS. Methods: The methodology involved analyzing neuroendocrine pathways and physical manifestations through PubMed, ScienceDirect, and Scopus databases. Findings indicate that PCOS is primarily characterized by androgen excess, ovulatory dysfunction, and disruption of the hypothalamic-pituitary-ovarian (HPO) axis. Hormonal dysregulation includes disturbances in GnRH, insulin, LH/FSH ratio, and androgens. GnRH stimulates LH and FSH release from the pituitary, regulating ovarian function, while Anti-Müllerian hormone (AMH) inhibits follicular development in PCOS. Conclusion: The review concludes by highlighting the hormonal alterations, including decreased frequency and amplitude of LH pulses, disruptions in GnRH, LH, and FSH. Genetic predispositions and disturbances in the LH/FSH ratio can lead to impaired follicle growth and polycystic ovaries. This comprehensive exploration underscores the importance of understanding the hormonal and neuroendocrine mechanisms underlying PCOS, contributing to better diagnosis and treatment strategies